Health literacy levels and views about being invited to a colorectal cancer screening program. (3rd June 2018) - Wangmar, Johanna; Jervaeus, Anna; Fritzell, Kaisa; Wångdahl, Josefin; Hultcrantz, Rolf; Wengström, Yvonne
Abstract: Background: Sweden has not yet implemented a national screening program for colorectal cancer, but a nationwide study is ongoing; the Screening of Swedish Colons (SCREESCO). Previous research shows that the use of health care services, together with several health-related outcomes, is associated with an individual's level of health literacy. However, the relation between health literacy and participation in colorectal cancer screening has produced varying results reported within the few studies addressing this issue and therefore, further research is warranted. Material and methods: The aim was to explore health literacy and views about being invited to screening, among participants and non-participants in a national colorectal cancer screening program. They were randomly sampled to fecal immunochemical test or colonoscopy and a mixed methods approach was applied, using questionnaires, focus group discussions and interviews. Results: The majority of individuals, whether they were participants or non-participants in the SCREESCO program, had an acceptable level of health literacy and no significant differences in health literacy levels between the groups were found. Participants expressed that it was important and appreciated to be able to choose information sources on an individual basis. Among non-participants, the importance of receiving invitations with a clear message that quickly draws one's attention was highlighted. However, both groups expressed a positive outlook towards the invitation. The mixed methods approach revealed that findings from interviews and focus group discussions corresponded to items in the health literacy scales. Conclusion: A majority of individuals displayed acceptable levels of health literacy, regardless of whether they chose to participate or not. Similarities between the groups were seen in the qualitative findings regarding views of the invitation. Currently, the SCREESCO invitation letter is distributed by regular mail, but in the future a more dynamic approach could be valuable to increase clarity in the message about importance of screening.